If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Z + 7z = 31 Solving Z + 7z = 31 Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '-7z' to each side of the equation. Z + 7z + -7z = 31 + -7z Combine like terms: 7z + -7z = 0 Z + 0 = 31 + -7z Z = 31 + -7z Simplifying Z = 31 + -7z
| 4y-2=-4 | | 0=20t+5t^2 | | 63=99 | | x^2+(2-2i)x-2i=0 | | 5f+3=-7 | | 3(5x+1)=3(1+5x) | | 5f-13=-7 | | 5n-9=2 | | 12z+4=2[5z+8]-12 | | -6ysinx=0 | | 4t+5=53 | | -2(3t+6)= | | 5n-9=-2 | | 4x-11=n+26 | | 2n-22=14-4n | | 4s-15=4s+11 | | 6x-5=12+1 | | v-6.39=8.53 | | 2X+4(3X-7)=112 | | 20+9w=4(15-w) | | 3y-5+2y=5 | | 2x+4y=40-16 | | (36a-6)=(4-24a) | | 7XY= | | x+2x=243 | | 4x+2y=40-16 | | Y=0.25x+3 | | -8pr+8q-10r+10=5q-5r+9 | | 2(x-4)+3=15 | | 4x+8=4(x+7) | | 6x+7x-x= | | 4d-16=20 |